Determinants of the Physical and Mental Workload of Nurses with the Implementation of Patient Safety during the Covid-19 Pandemic at Laburan Baji Hospital Makassar - Aulia Riski; Amran Razak; Reza Aril Ahri (PT.Mantaya Idea Batara, 2021)
Nurses have a very big responsibility in carrying out their duties both to patients and their families. During the current Covid-19 pandemic the number of patients received by hospitals is not proportional to the number of nurses so that it will have an impact on increasing physical and mental workloads. This study aims to determine the relationship between the determinants of the physical and mental workload of nurses with the application of patient safety during the COVID-19 pandemic at Labuang Baji Hospital Makassar.This type of research is a quantitative research with a cross sectional study approach. The sampling technique used total sampling with a total sample of 53 people. Data analysis was carried out univariate, bivariate with chi-square test. The results showed that there was an influence between physical workload (p value = 0.001) mental workload (p value 0.017) on the Application of Patient Safety during the Covid 19 Pandemic Period at Labuang Baji Hospital Makassar. It is recommended for nurses to perform stress management and adequate rest so that their workload is reduced so that the application of patient safety can be carried out properly.